Hydrogen effect on phase angle shift in electrochemical impedance spectroscopy during corrosion fatigue crack emanation. (18th November 2021) - Zhong, Xiankang; He, Yuantai; Eliaz, Noam; Campbell, Kyra Sedransk; Hu, Junying
Abstract: It is generally considered that hydrogen could accelerate the corrosion fatigue process, however, the effective monitoring approach for the corrosion fatigue development in the hydrogen related environment is still missing. In this work, the hydrogen effect on phase angle shifts in electrochemical impedance spectroscopy during corrosion fatigue crack formation in drill pipe steel was in-situ studied. The results show that phase angle shifts as a function of time could be used to monitor the corrosion fatigue development in the presence of hydrogen. The permeated hydrogen leads to a lower peak intensity and shifts the peak to a higher frequency on the phase angle vs . frequency curve. These differences are due to the formation of a corrosion fatigue crack with a shorter length than in the absence of hydrogen. The phase angle shift reveals that the presence of hydrogen results in shortening crack initiation time and corrosion fatigue life of the drill pipe steel. Highlights: Hydrogen leads to a lower peak intensity and shifts the peak to a higher frequency. Hydrogen causes the formation of a crack with shorter length than its absence. Hydrogen results in shortening crack initiation time and corrosion fatigue life.